If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g(x) = (3x + -4) + -1(-6 + 4x) Multiply g * x gx = (3x + -4) + -1(-6 + 4x) Reorder the terms: gx = (-4 + 3x) + -1(-6 + 4x) Remove parenthesis around (-4 + 3x) gx = -4 + 3x + -1(-6 + 4x) gx = -4 + 3x + (-6 * -1 + 4x * -1) gx = -4 + 3x + (6 + -4x) Reorder the terms: gx = -4 + 6 + 3x + -4x Combine like terms: -4 + 6 = 2 gx = 2 + 3x + -4x Combine like terms: 3x + -4x = -1x gx = 2 + -1x Solving gx = 2 + -1x Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by 'x'. g = 2x-1 + -1 Simplifying g = 2x-1 + -1 Reorder the terms: g = -1 + 2x-1
| 6-3x=6x-10x+8-2 | | 8x=3y | | w/4+3=7 | | (x+4)-7=x | | 60-3x=150 | | 2(2x+7)=42 | | 20x-8-14x+2=18x-9-12x+13 | | 9x+5y=82 | | x^2=4-3x | | 9-22.5=x | | 9x-13y=94 | | 7.25=2*3.14r | | x^2+6x-12=0 | | 2X-XY=-52-30X-40X | | -14=v-7-8 | | 15=3-2 | | 3x-12x+2=-25 | | (X+2)=9 | | v^4-4096=0 | | 14(t-6)+7t=7(3t+5)-11 | | 5(x+2)(x+2)+1=16 | | l+-3=9 | | 4c^2-0=0 | | 2y-x=3 | | 6-3=5x-10x+2 | | -4+19=3b-3-2b | | 6g-11=4g+4 | | 1x-21=4x+8 | | 8(3x-7)=20 | | -3(2s-4)-12=-2(6s+5)-2 | | 8322+9281= | | -9+x=17 |